Expanding border space improve both yield and stability in a high-density drip-irrigated spring wheat system in Xinjiang, China - Li, Xiaofang; Zhao, Yanhui; Ding, Bianhong; Ding, Haoyu; Qiu, Zhizhong; Ma, Xiaoqi; Yang, Yonghui; Wan, Wenliang (Frontiers in Plant Science, 2025)
Increasing planting density is regarded as one of the most effective strategies for enhancing wheat productivity. However, it also increases the risk of yield reduction owing to lodging. Preliminary findings suggest that border effects can improve lodging resistance in drip-irrigated wheat systems. Therefore, to maximize grain yield and lodging resistance, we modified the normal drilling sowing (P1, set as CK1) by expanding the border space (EBS) to 20 cm and obtained the corresponding EBS drilling sowing pattern of P2 (drilling sowing, EBS to 20 cm). We also modified the normal uniform sowing pattern (P3, set as CK2) by EBS to 20 cm and obtained the corresponding EBS uniform sowing pattern of P4 (uniform sowing, EBS to 20 cm). A two-year field experiment was conducted to evaluate the yield performance of four sowing patterns (P1–P4) across four planting densities: 570 × 104 plants ha−1 (D1), 630 × 104 plants ha−1 (D2), 690 × 104 plants ha−1 (D3), and 750 × 104 plants ha−1 (D4). In both years, the grain yield for all patterns initially increased with planting density and then declined. Compared to P1 and P3, the EBS patterns (P2 and P4) exhibited improved tolerance to high planting densities. Among the tested treatments, P4 pattern achieved the highest grain yield (8576–8779 kg ha−1), water use efficiency (15.5–16.0 kg ha−1 mm−1), and economic return (1991–2058 US$ ha−1) at D3. EBS enhanced canopy photosynthesis, optimizing the mobilization of pre-anthesis assimilates stored in vegetative organs toward grains during the filling stage. This redistribution mechanism sustained a high grain weight and spike number under high-density conditions. Furthermore, the improved photosynthetic capacity enhanced stem strength, thereby reducing lodging risk and improving yield stability. Additionally, uniform sowing promoted synchronous development of wheat spikes and reduced harvest losses. Overall, P4 was recommended for high-density drip-irrigated spring wheat systems because of its superior yield performance, stability, water use efficiency, and economic benefits.